Auto-proyección en la niñez temprana: un estudio sobre la congruencia entre la Memoria Episódica, el Pensamiento Futuro Episódico, la Teoría de la mente y la toma de perspectiva visual - Tomás-Llerena, Clementina (2025)
Children’s understanding of mental states and their temporal and spatial perspective-taking abilities change substantially during early childhood. It has been proposed that these abilities converge on common mechanisms based on self-projection. Also, remembering and prospection are thought to jointly support human capacity for mental time travel. This study explores the behavioral congruence of perspective-taking abilities by assessing episodic memory, episodic future thinking, theory of mind, and visual perspective-taking in 85 children aged four to six in Uruguay. We found no overall associations, except for theory of mind (false beliefs) and episodic future thinking. Results are discussed in the light of conceptual implications of the tasks, while we argue that enhancing equivalence in task design is essential for advancing future research.